Genotoxic and haematotoxic damage induced by ELF magnetic fields - Udroiu, Ion; Cristaldi, Mauro; Ieradi, Luisa Anna; Bedini, Angelico; Giuliani, Livio (European Journal of Oncology and Environmental Health, 2008)
Aim. To assess genotoxic and cytotoxic properties of extremely low frequency magnetic fields. Materials and methods. The micronucleus test was performed on peripheral blood sampled from newborn mice exposed to a 50 Hz, 650 μT magnetic field during the whole intra-uterine life (21 days) and from adult mice exposed for the same amount of time. Results. Chronic exposure caused an increase in micronuclei frequency and a decrease of polychromatic erythrocyte percentage in newborn mice but not in adults. Conclusions. This work underlines the necessity to further investigate the effects of magnetic fields on genome integrity and haemopoiesis.